Phytochemical screening and antihelminthic activity of leaf and root extracts of Cassia tora plant - Shrestha, Aashish; Ghimire, Kamana; Gupta, Amit Kumar; Pokhrel, Priyanka; Banerjee, Janmajoy; Khanal, Hemanta; Pradhananga, Mahalaxmi (Creative Pharma Assent, 2017)
Cassia tora is one of the most important sources of medicinally important phytochemicals and widely used in Ayurvedic and Chinese system of medicine. The fresh plants of cassia tora were collected from the different locality of Dharan, Sunsari district during the month of August. In this study leaves and root extracts were subjected to extraction by soxheletion by using ethanol and water and the extracts were subjected to antibacterial activity against Staphylococcus aureus. and Citrobacter koseri, the ethanolic extracts were screened for antihelmenthic activity against Indian adult earth worm (Pheretima posthuma) with a moderate result. The result of antibacterial activity revealed that aqueous extract of leaves and roots showed better activity in comparison to aqueous extracts particularly against gram positive bacteria (Staphylococcus aureus).